Design of a model of evaluation and measurement of organizational maturity in project management and application to companies of Colombian´s shipowners (2019)
The Project management organizational maturity models are considered a useful tool to evaluate the current capacity of organizations to manage and carry out successful projects, including its alignment with the organizational strategy. Through the literature review, it has been built up a new project management organizational maturity model called “Análisis Natural del Ambiente Institucional Sistematizado” ANAIS M2. This new model is based on maturity models such as OPM®, P3M3®, KPM3, P2M, CP3M©; and it is supported by 189 elements of valuation within the new model. Generating the action plan to follow, based on the elements of valuation which are not accomplished resulting from evaluation. Then the new model is tested with shipowner companies in Colombia, between 2013 and 2017, which carried out 907 projects and, as a result of evaluation, are classified as Level 2: Medium according to the ANAIS M2 maturity level. © 2019 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.